Karakterisasi Pertanian Berkelanjutan di Pulau Kecil - Zasti Indrianty Joisangadji; Rima Melati; Suratman Sudjud; Abdul Rahmat Mandea (Institut Pertanian Bogor, 2024)
The character of Hiri Island, which is located in the cluster of small islands in North Maluku in the study of sustainable crop cultivation practices, has yet to be documented in the Islands Agriculture database. This research reveals local farmers' cultivation practices using production inputs. The methods used are observation and interviews. Respondents were determined by deliberate methods. Research variables included sustainable agriculture indicators such as land conservation, agroforestry, integrated pest control, protective crops, crop nutrient management, and crop diversification. Data were obtained through a closed questionnaire with